Measuring Bargaining Power Through Grievance Outcomes : Results from an Ontario Steel Mill - Suschnigg, Peter (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1993)
This paper examines the dynamics and the impact of the Free Trade Agreement (FTA) between Canada and the United States within the context of Canada's primary steel industry. It is argued that Canada's leading primary steelmakers supported the FTA because of their belief that steel markets were increasingly continental, and, because of their ideological adherence to the neoconservative agenda of corporate business and the federal Progressive Conservative government. Steelworkers and their union, the United Steelworkers of America, opposed the FTA because of the loss of jobs that would ensue with its implementation and because of its larger "right wing" economic and political direction. The paper concludes that while — to this point — it is difficult to differentiate the specific impact of the FTA from factors associated with industrial restructuring in the steel industry as a whole, the FTA is increasingly the central economic and political factor in the deepening crisis of the Canadian steel industry.